Hubungan Antara Pola Makan dan Status Gizi Anak dengan Prestasi Belajar Siswa Kelas VII SMP Negeri 3 Ternate Kota Ternate Selatan - Harpina Harpina; Jena Andres (Jurnal Ilmiah Wahana Pendidikan, 2022)
School-age children have a period of rapid physical and psychosocial growth and development. To fulfill this, optimal nutritional status conditions are needed. Nutritional status is directly influenced by food consumption patterns and indirectly by parenting patterns, food availability, socio-economic factors, culture and politics. The psychosocial development of school-age children can be seen when children start choosing the food they choose. This will shape food consumption patterns in children. Imbalance in food consumption patterns will cause nutritional problems, both undernutrition and over nutrition. Unbalanced diet and nutritional status greatly affect learning achievement in children. This study aims to determine the relationship between diet and nutritional status with learning achievement of Class VII students of SMP Negeri 3 Ternate, City of South Ternate for the 2021/2022 academic year. This type of research is a quantitative study with a cross sectional design. The total population of the study was 142 students. The research sample was 50 students. The sampling technique is Simple Random Sampling. The research data uses primary data in the form of respondents' knowledge regarding nutritional status, interview guides, observations, documentation, measurements of weight and height, and secondary data in the form of student report card grades for the even semester of the 2021/2022 academic year. The results of the Chi-Square test showed that there was a significant relationship between eating patterns and learning achievement from the value of X2count> X2table which had a value of 0.739> 3.481 with a significance P=0.05. There is no relationship between nutritional status and academic achievement because the value of X2count < X2table is 0.224 <3.481 with a significance of P=0.05. A good diet affects learning achievement because it is one of the factors that determines success in learning, and a good diet and a variety of foods in everyday life contain nutrients that can increase concentration in learning better and students will be easier to accept lessons at school.